2021
DOI: 10.1002/cpt.2411
|View full text |Cite
|
Sign up to set email alerts
|

Identifiability of Biologicals: An Analysis Using EudraVigilance, the European Union's Database of Reports of Suspected Adverse Drug Reactions

Abstract: Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? A high level of commercial name identifiability on all reports of adverse drug reactions (ADRs) is important to ensure timely and effective discrimination of products. The increased availability of biosimilars in Europe and potential changes in reporting practices over time might influence identifiability. It is, therefore, important to regularly monitor the level of identifiability. WHAT QUESTION DID THIS STUDY ADDRESS? We investigated the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These deviating or missing results did not preclude approval, as similarity was shown for the relevant QAs and in dedicated PK studies and confirmed by clinical data in the efficacy study. As this paper analysed already approved biosimilar products, and subsequent experience with these products to date has not resulted in any safety or efficacy issues following their approval, 16,55,56 it can be concluded that the regulatory decisions taken were correct.…”
Section: Articlementioning
confidence: 89%
See 2 more Smart Citations
“…These deviating or missing results did not preclude approval, as similarity was shown for the relevant QAs and in dedicated PK studies and confirmed by clinical data in the efficacy study. As this paper analysed already approved biosimilar products, and subsequent experience with these products to date has not resulted in any safety or efficacy issues following their approval, 16,55,56 it can be concluded that the regulatory decisions taken were correct.…”
Section: Articlementioning
confidence: 89%
“…Furthermore, the EU pharmacovigilance systems and risk management planning are sufficiently robust 16,55,56 to detect safety signals in postmarketing use. However, safety signals (including reports on reduced efficacy) are not anticipated, because more than a decade of clinical experience indicates that a new safety signal solely identified with a biosimilar is extremely unlikely 55,56 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation